The Efforts of Teachers of Al Islam in Improving The Good Ethic of VII Grade of The First Middle School of Muhammadiyah 11 Surabaya - Arief Himawan; Zainuddin Maliki (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This research was conducted because it was motivated by the problems that occur in students at this time, ranging from brawls, harassment, sexual intercourse, bullying, moral crisis and others. This has led many parties to highlight the role of education, meaning that events in society cannot be separated from the role of education. The formulation of the problem of this thesis is first, how is the implementation of the efforts of Al Islam teachers in improving the morality of the students of Muhammadiyah 11 Surabaya Junior High School. Second, how is the application of religion values in the daily activities of SMP Muhammadiyah 11 Surabaya students, Third, what are the supporting and inhibiting factors of implementation the values of morality and religion in daily activities at SMP Muhammadiyah 11 Surabaya. This type of research is field research which collects primary data through interviews from the principal, teachers of SMP Muhammadiyah 11 Surabaya, and guardians of SMP Muhammadiyah 11 Surabaya students, while secondary data is obtained from the literature and documents of SMP Muhammadiyah 11 Surabaya, after all data is collected in further analysis qualitatively and described in descriptive form. The results of the study concluded that the activities of the teacher's efforts to improve morality showed satisfactory results, namely the inclusion of the values of humanism, manners and morality, while the things that support are the policies of the principal, educators, school friends, family, facilities and infrastructure as well as the factors that become obstacles, are schoolmates, facilities and infrastructure and family.